Small business taxes made easy : how to increase your deductions, reduce what you owe, boost your profits, and build a dynasty - Rosenberg, Eva (McGraw Hill Education, 2017)
This go-to tax guide for small-business owners is packed with tips for dramatically lowering your taxes. This new edition covers key provisions passed by Congress that will affect your taxes for 2016 through 2020.